1962
DOI: 10.2307/3894914
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Herbage Weight in an Annual Grass Community

Abstract: Herbage production is important to all concerned with range land. The range conservationist aims to grow the largest amount that can be used efficiently. The rancher must do the harvesting. The research worker tries to evaluate the herbage production processes. All are interested in the rate of herbage growth, the maximum production reached, and the decline in available herbage during the dry season. Much research into the California annual type stipulates sampling at the time of maximum weight. If the moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1966
1966
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Sampling periods should, therefore, correspond to the growth period(s) of specific phenological groups containing these key management species. Less precise sampling schemes necessarily confound maximum herbage production with normal, seasonal changes in herbage accumulation and/ or weathering (Ratliff and Heady 1962). Similarly, proper livestock stocking rates within pastures should be based on forage available during the period of grazing rather than on peak forage production, which may occur either before or after period(s) of livestock grazing.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling periods should, therefore, correspond to the growth period(s) of specific phenological groups containing these key management species. Less precise sampling schemes necessarily confound maximum herbage production with normal, seasonal changes in herbage accumulation and/ or weathering (Ratliff and Heady 1962). Similarly, proper livestock stocking rates within pastures should be based on forage available during the period of grazing rather than on peak forage production, which may occur either before or after period(s) of livestock grazing.…”
Section: Discussionmentioning
confidence: 99%
“…percent composition also positively correlated with freezing temperatures during the early fall period marked by September, October, and November (Tables 3 and 4). Ratliff and Heady (1962) indicated that Bromus mollis initiated growth sooner than other species in the annual type. The change from beneficial to detrimental influences of freezing temperatures occurs some time during November.…”
Section: Although Warm Winter Temperatures Encouraged the Survival Ofmentioning
confidence: 99%
“…Ratliff and Heady (1962) studied the effect of phenological development of annual species and observed that some species began their most rapid period of growth earlier than others, and some lost weight earlier than others. Ratliff and Heady (1962) studied the effect of phenological development of annual species and observed that some species began their most rapid period of growth earlier than others, and some lost weight earlier than others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of temperature and rainfall patterns on the floristic composition and biomass of mediterranean pastures is well known (e.g. Ratliff & Heady 1962;Hooper & Heady 1970;Murphy 1970;Duncan & Woodmansee 1975). Talbot, Biswell & Hormay (1939) differentiated grass, filarée and clover years, which are closely correlated with precipitation.…”
Section: Introductionmentioning
confidence: 99%